A comparison of caregiver burden in older persons and persons with Parkinson's disease or dementia in sub-Saharan Africa. (April 2014) - Dotchin, C.L.; Paddick, S.-M.; Longdon, A.R.; Kisoli, A.; Gray, W.K.; Dewhurst, F.; Chaote, P.; Dewhurst, M.; Walker, R.W.
ABSTRACT Background: Caregiver burden includes the many physical, mental and socio-economic problems arising from caring for individuals with chronic and disabling diseases. Being a carer in sub-Saharan Africa (SSA), where little is known about chronic neurological conditions, may be extremely demanding. Conversely, multigenerational living may allow sharing of care among many caregivers. We wished to determine the relative burden of caring for two chronic neurodegenerative conditions (Parkinson's disease (PD) and dementia) in rural Tanzania. Methods: All surviving patients from a PD prevalence study, newly identified people with PD from a neurological disorders study and all people with dementia from a dementia prevalence study in Hai, rural Tanzania, were invited to participate. The Zarit Burden Interview (ZBI) was used to determine level of caregiver strain (higher score reflects more strain). Results: Of 25 PD patients ZBI was recorded in 20 (14 male). Five had no identifiable carer as they were largely independent. Three had PD dementia (PDD). Of 75 people with dementia (excluding 3 PDD), 43 (32 female) completed the ZBI. For the other 32, the caregivers felt the care they provided was a normal intergenerational expectation. Median ages were 78.5 and 85 years for PD and dementia, respectively. Median ZBI was 30.5 for PD and 14 for dementia (U = 166.0, z = –3.913, p < 0.001). Disease duration and disease type (PD or dementia) were univariate predictor of ZBI score, although only disease type was predictive by multivariable linear regression. Conclusions: Caring for an individual with PD may be more burdensome than caring for an individual with dementia in SSA. People with more advanced PD had higher caregiver burden.